A hierarchical theoretical model for mechanical properties of lath martensitic steels. (December 2018) - Yu, Long; Xiao, Xiazi; Chen, Lirong; Cheng, Yangyang; Duan, Huiling
Abstract: Lath martensitic steels possess excellent mechanical properties because of the special microstructure, i.e. laths, blocks and packets with particular crystallography in a prior austenite grain. To theoretically analyze the mechanical behavior of lath martensitic steels, a hierarchical model is proposed combining the crystal plasticity theory and micromechanical method. Within the crystal plasticity theory, an interfacial dislocation model is proposed at the block level to physically describe the effect of lath boundary on the deformation behavior. Furthermore, The scale transition among block, prior austenite grain and lath martensitic steel is accomplished by the elastic-viscoplastic self consistent theory. Based on the proposed model, the deformation behavior of lath martensitic steel with hierarchical structures has been theoretically analyzed. It is revealed that the deformation anisotropy of prior austenite grain is weak due to the particular crystallography of microstructures, and the influence of temperature on yield stress is dominated by the thermally related intrinsic lattice friction and elastic modulus. Moreover, the hierarchical model is generalized to study the mechanical behavior of irradiated lath martensitic steel, and it is found that the change of temperature has a limited effect on the irradiation hardening behavior, and the increase of yield stress induced by irradiation-induced defects can accelerate the evolution rate of dislocation density. Numerical results with/without irradiation effect can both match well with corresponding experimental data, indicating the good accuracy and rationality of the proposed model. Highlights: An interfacial dislocation model is proposed to describe the effect of lath boundary on the deformation behaviors. A hierarchical theoretical model is proposed to study the hierarchical mechanical behavior of lath martensitic steel. Based on the proposed model, the mechanical behaviors of unirradiated/irradiated lath martensitic steel are analyzed.